Empowerment of Culinary Potential in the Community of Tanjung Lanjut, Continued Muaro Jambi - Assobary, Alfanna Ibnu; Silalahi, Resita Grace Nauly Br; Maisyarah, Nyimas Dian; Nabila, Repa; Komaronnisa, Basrida; Berlian, Putri (Jurnal Pengabdian Masyarakat Bestari, 2024)
Tanjung Lanjut Village has untapped potential, both in terms of natural beauty, as well as abundant natural resources that are not widely known by the local community, especially dragon fruit. Dragon fruit is an agricultural commodity that is increasingly popular among the community. Dragon fruit not only has a delicious taste, but is also rich in nutrients and health benefits. However, community empowerment in Tanjung Lanjut Village in processing the potential of the Dragon Fruit itself has not been optimal. By conducting community service and involving the community in decision-making, this program aims to help the local community benefit from the creative economy sector, especially in the culinary field.